The Category of "Perception" in the Professional Activity of a Social Worker (Aesthetic Aspect) - Vasianovych, Hryhoriy; Nahirniak, Mykhailo (Journal of Vasyl Stefanyk Precarpathian National University, 2023)
The professional activity of a social worker is multifaceted, in which the aesthetic aspect has a special place. The key reason is that it aims to reveal the personality with special needs, the beauty of human existence, its inexhaustible possibilities of cognition and self-knowledge, development, and self-improvement. It is especially important for a social worker to help such a person perceive this world adequately, sometimes even overcome the tragedy of their existence, live a full spiritual and social life, and realize their inner potential. Of course, all this requires the proper formation of moral and aesthetic, psychological and pedagogical, and general culture from the social worker. Instead, today the contradiction between man and his culture is becoming more and more obvious. There appeared even the expression "civilization without culture", which testifies to a significant decrease in the importance of the aesthetic in almost all spheres of human life, its gradual descent from the arena of strong social activity and moving to the periphery of public life, the loss of considerable civic attention to it. It is enough to say that the subject "Pedagogical Aesthetics" has not been taught for years in the system of humanitarian education, which includes its fundamental branch - social work. In our deep conviction, this hurts the consciousness of both social workers and their patients, especially in the aspect of aesthetic perception of reality.